The Role of Incentives in Indonesia Special Economic Zone (Case in Sei Mangkei, North Sumatera Province) - Tarigan, Reffoni Mastaria (Jurnal Ilmiah Administrasi Publik, 2019)
This research using interview and document review to explore how far the role of incentives in Indonesia Special Economic Zones (SEZ) and how far the incentives can attract investments. This research was conducted in SEZ Sei Mangkei, North Sumatera Province, an SEZ that develop as the first industrial SEZ in Indonesia. The result showed that the most important incentive in SEZ is the integrated infrastructure, especially the establishment of seaport and railways which are connected to the SEZ and international trade line. Moreover, the investment in SEZ Sei Mangkei increased significantly after the basic infrastructure was developed in 2015. This study showed that collaboration among government and zone developers is necessary for accelerating the infrastructure development of SEZ.